(untitled) (XXI Century. Spanish Literature and Culture)
This essay explores the notion of poetry as thought and perception as creation, as well as the influence and importance of María Zambrano and the new ways of understanding philosophy, based on the need to consider poetic reason in all kinds of intellectual research and aesthetic understanding. It also presents poetry as an evolutionary concept connected to life and other branches of knowledge such as philosophy, science or art.